Google Translate Mengubah Bahasa Batak Menjadi Bahasa Indonesia - Calvin Calvin; Piter Antonius; Saut Dohot Siregar (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Google Translate is an artificial intelligence-based translation service developed by Google. Since its introduction in 2006, this service has continued to create with the application of Neural Machine Translation (NMT) technology, which improves the accuracy and fluency of translation compared to previous methods. This study aims to determine the effectiveness and limitations of Google Translate in translating Batak into Indonesian. The research method used is descriptive qualitative with a comparative approach of Google Translate translation results and manual translations by professional translators. The study results show that Google Translate can translate basic words and simple sentences quite well. However, there are several limitations, such as a lack of understanding of the cultural context, idioms, and dialect variations in the Batak language. In addition, the translation is also influenced by the limitations of the database and vocabulary enrichment in this service. Thus, although Google Translate can be a tool in translation, users still need to do manual verification to ensure accuracy, especially in fields that require high precision such as law, academics, and professional communication.